THE INTEGRATION OF AUGMENTED REALITY IN MARKETING:ENHANCING CUSTOMER EXPERIENCE AND BRAND ENGAGEMENT: LITERATURE REVIEW - Kurnia Budhy Scorita; Nenden Hendayani; Muhammad Ari Kusuma; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Augmented Reality (AR) has emerged as a transformative technology with significant implications for marketing practices. This literature review explores the integration of AR in marketing strategies and its impact on enhancing customer experience and brand engagement. Drawing on a comprehensive review of scholarly articles, industry reports, and case studies, this paper synthesizes existing research to provide insights into the potential of AR to revolutionize marketing interactions. Key themes explored include the immersive nature of AR experiences, consumer attitudes toward AR marketing content, strategic considerations for AR implementation, and the role of AR in shaping brand- consumer relationships. The review highlights the importance of designing compelling and contextually relevant AR experiences that resonate with consumers and drive brand engagement. Moreover, it examines the challenges and opportunities associated with AR marketing, such as content saturation, technological constraints, and privacy concerns. By synthesizing empirical evidence and theoretical frameworks, this review offers valuable insights for marketers seeking to leverage AR technology effectively in their campaigns and initiatives. The findings underscore the transformative potential of AR in creating immersive brand experiences, fostering emotional connections with consumers, and driving brand equity in the digital era.